Distributions of strong ground motion due to dynamic ruptures across a bimaterial fault: Implications for seismic hazard analyses. (1st December 2016) - Yuan, Jie; Zhu, Shoubiao
Highlights: Spontaneous rupture along a bimaterial interface is simulated. Strong ground motion is asymmetrically distributed across a fault with bimaterial interface. Peak ground acceleration in the compliant area is greater than that in the stiffer region. Peak ground acceleration is larger on the side in positive direction. Bimaterial effect is important in seismic hazard assessment. Abstract: We perform 2-D finite element calculations of mode II rupture along a bimaterial interface governed by regularized rate- and state-dependent friction law, with the goal of understanding how the bimaterial interface influences the strong ground motion. By comparison with properties of rupture in a homogeneous solid, we found that bimaterial mechanism is important for earthquake ruptures and influences the strong ground motion significantly. The simulated results show that mode II rupture evolves with propagation distance along a bimaterial interface to a unilateral wrinkle-like pulse in the direction of slip on the compliant side of the fault, namely in the positive direction. Strong ground motion caused by seismic waves emanated from the rupture propagation is asymmetrically distributed in space. The computed peak ground acceleration (PGA) is high in the near-fault region. Particularly, PGA is much larger in the region on the side in the positive direction. In addition, it is greater in the more compliant area of the model than that in the stiffer area with corresponding locations. Moreover, the differential PGA due to bimaterial effect increases with increasing degree of material contrast across the fault. It is hoped that the results obtained in this investigation will provide some implications for seismic hazard assessment and fault rupture mechanics.